Compartmental Strabismus. Issue 3 (2nd July 2020) - Pineles, Stacy L.; Chang, Melinda Y.; Velez, Federico G.
ABSTRACT: Recent reports confirm innervational compartments of select rectus extraocular muscles as well as the superior oblique. 1 Histopathological and orbital imaging studies demonstrate well defined compartmental innervation of the horizontal rectus muscles with less differentiation in the vertical rectus muscles. Acquired vertical misalignment not associated with cyclovertical muscle dysfunction has been associated with horizontal rectus muscle compartment dysfunction. Pattern and other forms of strabismus have been associated with segmental or compartmental abnormal innervation of the extraocular muscles. Taking advantage of segmental function and innervation, selective weakening and strengthening procedures have been used to treat patients with incomitant near/distance disparities, incomitant vertical and torsional strabismus, and patients with A- and V-pattern strabismus